Nutrition for winter sports - Meyer, N. L.; Manore, M. M.; Helle, C. (Journal of Sports Sciences, 2011)
Winter sports are played in cold conditions on ice or snow and often at moderate to high altitude. The most important nutritional challenges for winter sport athletes exposed to environmental extremes include increased energy expenditure, accelerated muscle and liver glycogen utilization, exacerbated fluid loss, and increased iron turnover. Winter sports, however, vary greatly regarding their nutritional requirements due to variable physiological and physique characteristics, energy and substrate demands, and environmental training and competition conditions. What most winter sport athletes have in common is a relatively lean physique and high-intensity training periods, thus they require greater energy and nutrient intakes, along with adequate food and fluid before, during, and after training. Event fuelling is most challenging for cross-country skiers competing in long events, ski jumpers aiming to reduce their body weight, and those winter sport athletes incurring repeated qualification rounds and heats. These athletes need to ensure carbohydrate availability throughout competition. Finally, winter sport athletes may benefit from dietary and sport supplements; however, attention should be paid to safety and efficacy if supplementation is considered.